Pemanfaatan Bakteri Selulolitik Sekum Kelinci dengan Aras Konsentrasi Koloni dan Waktu Inkubasi untuk Fermentasi Limbah Agroindustri Lokal dalam Pakan Kelinci - U. Ali, U.; Wajdi, M. F. (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
This study aims to isolation, characterization and create a culture of cellulolytic bacteria fromthe caecum of rabbits to fermentation local agro-industry waste CSO (skin coconut meat, soybean seed coat and onggok) into quality feed products and palatable as a commercial feedstuff substitute for optimization performance of rabbit. The materials of study are rabbit caecum, culture media and waste CSO. The study methods is descriptive of isolation, characterization and creation of caecum cellulolytic bacterial culture, continued experiments using a completely randomized design (CRD) factorial 3 x 5 fermentation of cellulolytic bacteria colonies concentration (Ci = 10 CFU / g DM, C2 = 108 CFU / g DM, C3 = 109 CFU / g DM) and a long incubation (Ii = 2 days, I2 = 4 days , I3 = 6 days , I4 = 8 days, I5 = 10 days). The results show that cellulolytic bacteria strongest from epithelial wall of caecum are gram-positive, do not form spores, catalase negative and bacillus. The nutrient content of waste CSO: CP 10.11%; CF 20.99%; EE 31.52%; NDF 33.42%, ADF 21,35% and cellulose 11.97% so need to be fermented. Treatment of bacterial colonies concentration and long Pemanfaatan Bakteri Selulolitik ... (Ali dan Wadjdi) incubation in fermentation CSO partially lowered OM, EE, CF, NDF, ADF and cellulose, but increase the CP. Treatment interaction increases CP and other nutrients down not significant. Effective treatment interaction concentration 108 CFU / g DM and long incubation 8 days with CP 11.55%; CF 17.34%; EE 31.29%; NDF 28.23% ; ADF 18:33% and cellulose 8.89%. In conclusion, the strongest rabbit caecum cellulolytic bacteria from the epithelial wall of the caecum are gram positive, not sporulating, catalase negative and formed bacillus. Nutrient content of the best CSOF at K2I8treatment with CP increased 14.36% and other nutrients down: CF 17.39%; EE 0.73%; NDF 15.53% and cellulose.25.74%. Suggested fermentation effectiveness CSO waste can use the caecum cellulolytic bacteria concentration of 10 CFU / g DM material and incubation time of 8 days.Keywords: CSO waste, fermentation, nutrient content.